Analisis Kuantitatif Kelengkapan Pengisian Formulir Assesmen Rawat Inap Obsgyn di RS X Jember - Irfiah Irfiah (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
The process of providing hospital plenary services has the role of many parties, one of which is the role of medical record management. The results of the assessment of the completeness of filling out the obsgyn inpatient assessment form at Hospital X still contained deficiencies (incomplete) which in this case had not reached the minimum standard of hospital services, which had to be 100%. The aim of this study was to analyze the completeness of the completeness of the filling out of the inpatient obsgyn assessment form at X Jember Hospital. This type of research uses descriptive research with a retrospective approach. The object of research is the obsgyn inpatient assessment form at X Jember Hospital for the 2022 period, totaling 1035 medical record files. The method of collecting data in this study is observing the components of identification, important reporting, authentication, and correct documentation and the analysis used is using quantitative descriptive analysis. The results of the identification component analysis with the highest completeness of 97.34%, and the highest incompleteness of 82.15%; important reporting components with the highest completeness of 93.91% and the highest incompleteness of 35.17%. The results of the authentication component analysis with the highest completeness were 75.17% and the highest incompleteness was 58.26%; the correct documentation component with the highest score of 92.46% and incorrect documentation with the highest score of 8.99%.